2019
DOI: 10.1093/geroni/igz038.348
|View full text |Cite
|
Sign up to set email alerts
|

Tau-Induced Astrocyte Senescence: A Novel Mechanism for Neuronal Dysfunction in Alzheimer’s Disease

Abstract: Chronic sterile inflammation is a pathological feature of Alzheimer’s disease (AD) and other neurodegenerative diseases. The mechanisms that drive neuroinflammation and its impact on AD progression are still incompletely understood. The accumulation of molecular damage in somatic cells can trigger cellular senescence, an irreversible state of cell cycle arrest accompanied by the expression of proinflammatory mediators known collectively as the “senescence-associated secretory phenotype” (SASP). Misfolded tau f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been shown that the clearance of senescent astrocytes from a mouse model of tau-dependent ND prevented the degeneration of cortical and hippocampal neurons and preserved cognitive function [216]. Recently, it has also been reported that tau is responsible for astrocyte senescence, which further contributes to synaptic dysfunction and neuronal loss in AD [217]. In addition, tau has a direct role in the induction of astrocyte senescence, probably through p53 activation [207].…”
Section: Senescent Astrocytes and Age-related Neurodegenerative Diseasesmentioning
confidence: 99%
“…It has been shown that the clearance of senescent astrocytes from a mouse model of tau-dependent ND prevented the degeneration of cortical and hippocampal neurons and preserved cognitive function [216]. Recently, it has also been reported that tau is responsible for astrocyte senescence, which further contributes to synaptic dysfunction and neuronal loss in AD [217]. In addition, tau has a direct role in the induction of astrocyte senescence, probably through p53 activation [207].…”
Section: Senescent Astrocytes and Age-related Neurodegenerative Diseasesmentioning
confidence: 99%
“…Interestingly, studies from the 1970s observed that lithium was a MSA, raising interesting questions about its established antiviral and neuroprotective properties ( Matsunaga et al., 2015 ; Murru et al., 2020 ; Chen et al., 2021 ). Indeed, lithium reverses pTau-induced astrocytic senescence and enhances T-cell function, suggesting senolytic properties ( Bhattacharyya and Wolff, 1976 ; Kucharz et al, 1988 ; Olson et al., 2019 ; Viel et al., 2020 ). This is significant, as lithium can reverse the virus-induced damage of tubulin, a key molecule in T cell activation ( Kopf and Kiermaier, 2021 ).…”
Section: Treatment Strategies For Pathological Cell-cell Fusionmentioning
confidence: 99%